A speed limit advisory system provided by in-vehicle HMI considering auditory perception characteristics for connected environment. (January 2023) - Xu, Qingjin; Fu, Rui; Wu, Fuwei; Wang, Biyao; Chen, Tao
Highlights: We proposed frontal distance models of auditory warning and examined the effects of a SLAS on driving performance. The SLAS received and transmitted the speed limit warning information from roadside infrastructure to specific driver. The SLAS led to smooth and effective deceleration, particularly in gradient audio-visual mode. The SLAS was particularly effective for drivers with low driving age (<10 years) and got a satisfactory evaluation. Apart from a safety benefit, the SLAS did not distract drivers or had any adverse effects on driving performance. Abstract: In-vehicle HMI (Human Machine Interface) systems are well studied due to their great application prospect, but the recent development of connected technologies raises more possibilities that this technology provides more accurate speed limit warnings to ensure driver safety according to specific vehicle and road parameters. To capitalize on the potential of in-vehicle HMI systems to provide auditory and visual warnings to drivers and to improve adoption and utilization of this warning information. To this end, we designed a speed limit advisory system (SLAS) that recommended reduced speeds for hazardous sections of road, communicated to drivers by their in-vehicle HMI systems. Frontal distance models of single and gradient auditory warning were implanted into the systems to determine the warning timing. We then tested these SLASs in a high-fidelity simulator in order to evaluate their utility. 70 participants (mean age = 28.7 years; 36 male) drove through a simulated 15 km stretch of one-way two-lane rural road. We evaluated five different warning modes: single visual (SV), single audio visual (SAV), gradient visual (GV), gradient audio visual (GAV) or control (roadside sign). Participants using the SLAS slowed down significantly compared to the control group before entering the curve, with drivers receiving GAV warnings driving lowest speeds. Less experienced drivers exhibited higher compliance with GAMs (GV or GAV). The SLAS was generally considered useful though not by drivers with>10 years of driving experience. Drivers tended to prefer singular warnings to gradated warnings, which were rated as equally preferable to roadside signage. Eye tracking data indicated that none of the SLAS modes were overly distracting to the drivers. Overall, we find that the SLAS improves driver safety while producing no obvious distraction. The main difficulty lies in persuading experienced drivers to use the system. In a word, the results of this study provide validation for the concept of HMI warning system using connected technology in hazardous road areas and help determine the appropriate timing of in-vehicle warnings.